Evaluation of the impact of the COVID-19 pandemic on routine care of people with chronic disease: a qualitative study - AYVAZ, İLKNUR; ALTAŞ, ZEYNEP MEVA; SAVE, DİLŞAD (My University, 2023)
Background and Objective: Restrictions in the COVID-19 pandemic have affected access to healthcare and caused delays in the routine care of people with chronic diseases. The aim of our study is to reveal the impact of the COVID-19 pandemic on routine care of people with chronic diseases. Methods: Our qualitative study was carried out with 12 people who came to the Cardiology outpatient clinics of tertiary Training and Research Hospital in June 2022 for a routine care due to their chronic diseases. As a data collection tool, a semi-structured questionnaire was used. The data were collected through face-to-face interviews with the participants by taking the necessary protective measures. Thematic analysis method was used in the analysis of the data. After the interviews were transcribed, each transcript was coded using the ATLAS.ti program. The ethics committee approval of the study was obtained. Results: The ages of participants were between 34-73, and 8 of them were male. Participant experiences were categorised into four themes: General Health Status, Routine Care during the Pandemic, Chronic Disease Management during the Pandemic and Patient Expectations of Healthcare. Most of the patients delayed their routine care during the pandemic and their chronic diseases worsened. Among the reasons for not going to the controls, the fear of contagion came to the fore, while some participants mentioned that they could not find an appointment. In terms of their expectations of healthcare, they stated that health institutions should give priority to those with chronic diseases and home health services and online services will provide convenience for them. Conclusion: Delaying hospital admissions for routine care made the management of chronic diseases difficult and worsened the chronic diseases of patients in the long term. Implementation of online health services such as telemedicine can facilitate chronic disease management.
Keywords: Sağlık Bilimleri; Health Sciences; Klinik Tıp (MED); Clinical Medicine (MED)